Efectos del regimen de corte y perfil de la herramienta sobre La rugosidad superficial en el torneado de aleaciones Co-28cr-6mo de uso biomédico - Castro Zavaleta, Santos Homero (2017)
As the cutting regime and tool geometry on surface roughness influence the turning of the Co-28Cr-6Mo alloys used as biomaterials was investigated. The purpose was to recommend optimum machining conditions that produce standardized roughness in biomedical implants. The study material was acquired as ø38 x 6m rods. From these bars, test specimens of Ø30x200 mm were made. These measures were selected in order to meet the requirement of ISO 3685 and avoid vibrations. The tests were carried out on a MILLTRONICS lathe (CNC) model ML-16. The cutting conditions were: Vc = 50, 75 and 100 m / min; A = 0.1, 0.15 and 0.25 mm / rev; P = 0.5, 0.7, 09 mm, R (insert edge radius) = 0.4, 08, 1.2 mm. The roughness measurements were performed using the SURFTEST-210 MITUTOYO Rough Meter. At the end of each turning operation, the average roughness values of the cylindrical surface shall be taken taking a cut distance of 2.5 mm for the measurements. The results show that for these alloys, the finer values of roughness are not always found with small advances, low depth, and high speeds as with metals. It depends on the integrated set of all variables where, like metals, advancement and radius of edge are the most influential variables. The minimum roughness value in all the tests was: 0.82 μm; was found using a radius insert "R = 0.8 mm, and cutting regime: [V = 50 m / min; A = 0.1 mm / rev; P = 0.7 mm]. The most influential variable in the roughness is the advance, followed by the cutting edge radius. A lower feed decreases the roughness, and the same happens when the edge radius increases. The cutting speed exerts a greater influence than the depth. No smooth surfaces have been achieved: (Ra <0.5 mm); but, it has been achieved minimally rough surfaces: (0.5 <Ra <1 μm); These were presented with inserts R = 0.8 and R = 1.2 under 6 different cutting conditions. Moderately rough surfaces: [1.0 and 2.0 μm] were found in 36 trials out of a total of 81. Finally, it was found that of all the tests (~ 50%) meets the standards required for biomedical implants with regard to roughness. It is concluded that in many cases it is not necessary to coat the implants to be able to use them, they can be used directly after a fine machining.